Barrier and successful factor of IBS system (case study in hostel construction, UiTM Pulau Pinang) / Siti Hafizan Hassan, Mohamad Zain Hashim and Janidah Eman - Hassan, Siti Hafizan; Hashim, Mohamad Zain; Eman, Janidah (2011)
The Industrialized Building Systems (IBS) concept was adopted and applied during early sixties in Malaysia. There are need to identify reason of the unresponsive and uninterested local contractor to the IBS. This study identifies knowledge of IBS components among respondents. The methodology adopted for the study includes literature review, observation and questionnaire survey. These questionnaires were distributed to the respondents, which represent the construction industry players in Penang. This study identified the level of knowledge and understanding of IBS system among the construction player. The study had been concluded that the level of understanding and knowledge of respondents on industrial building systems are in medium level. The study also evaluated the opinion of respondents on advantages of IBS. There are five main advantages that most agreed by respondents. There are (l) Good Quality Control, (II) Faster Completion, (III) Easy Installation, (IV) Reduce Time and (V) Higher Quality. Those five advantages of IBS should be promoted by the authority in order to attract more IBS users.